Polyplacophoran Assemblages in Shallow Waters of the West Antarctic Peninsula: Patterns of Diversity, Composition and Abundance - Christian M. Ibáñez; Sebastián Rosenfeld; Ivka Carvajal; Jennifer Catalán; Germán Zapata-Hernández; Manuel Gacitúa-Leible; Rocio Vargas; Pamela Morales; Angie Díaz; Sergio A. Carrasco; Javier Sellanes; Sadie Mills; et al. (Ecologies)
For the first time, field surveys for exploring the diversity and composition of shallow-water polyplacophorans in West Antarctica have been conducted. During the austral summer sampling campaigns of 2022, 2023 and 2024, a total of 1717 specimens of four species were collected from 21 localities. The composition, abundance, and diversity estimate of the assemblages showed that richness decreased southward due to changes in species composition. The ordination analysis showed a high similarity among localities. Thus, of the seven shallow-water chiton species previously recorded in Antarctica, only four were recorded here. Of them, Tonicina zschaui, Leptochiton kerguelensis, and Hemiarthrum setulosum were the most common and abundant, while Callochiton bouveti was the rarest and least abundant species. The diversity of shallow-water polyplacophorans in this area of Antarctica is low compared to the higher number of species reported in other sub-Antarctic regions. It is suggested that the effect of ice cover on shallow-water habitats could affect the abundance and diversity of chitons. In turn, the high similarity of assemblages may be due to the transport of larvae and juveniles by ocean currents and rafting between the studied sites.